Processing of Nutmeg Skins into Sweets to Develop the Creative Economy of the Cijeruk Village Community - Nuriyah, Winda; Risna, Siti Nurahmah; Novi Silmi, Pebriyani; Hasanah, Nauriatul; Fika, Rafikawati; Widya, Imardhea; Lestari, Asti Tri (AbdimasMu UMTAS, 2023)
One of the uses of nutmeg skin is to process it into sweets. This community service was carried out in Cijeruk Village, Dayeuh Luhur District, Cilacap Regency, Central Java Province. The implementation of this community service activity aims to determine the extent to which the community develops nutmeg so that it can become a source of community economy. The people in Cijeruk Village only use the seeds and mace so that the nutmeg skin itself is not used as an economic source. With the condition of the people who have limited knowledge, we took the initiative to make sweets made from nutmeg skin as the use and material for the community's economy in the future. The implementation of this community service activity began by looking for samples of nutmeg skins that could be made into sweets by asking for help from the heads of farmer groups in Cibengang Hamlet. After getting a sample of nutmeg skin, we immediately started the process of making candied nutmeg skin so that it could be immediately socialized and become a source of community income. The results of this community service show that public knowledge in the field of nutmeg increases with the socialization of making candied nutmeg peel. Therefore, people will increase their economic income by marketing candied nutmeg peel